2017
DOI: 10.1111/evo.13242
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and postcopulatory sexual selection favor aggressive, young males in polyandrous groups of red junglefowl

Abstract: A challenge in evolutionary biology is to understand the operation of sexual selection on males in polyandrous groups, where sexual selection occurs before and after mating. Here, we combine fine-grained behavioral information (>41,000 interactions) with molecular parentage data to study sexual selection in replicated, age-structured groups of polyandrous red junglefowl, Gallus gallus. Male reproductive success was determined by the number of females mated (precopulatory sexual selection) and his paternity sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 99 publications
(222 reference statements)
8
87
1
Order By: Relevance
“…But pre-copulatory and post-copulatory sexual selection can favour different traits (Evans & Garcia-Gonzalez, 2016), so it is unclear whether a female preference for older males translates into greater male reproductive success, or higher female fitness. In particular, older males might produce ejaculates that are less successful under sperm competition (McDonald, Spurgin, Fairfield, Richardson, & Pizzari, 2017), or might be less fertile thereby lowering the reproductive output of monogamous females (Carazo, Molina-Vila, & Font, 2011;Dean et al, 2010). Furthermore, the accumulation of germline mutations might reduce the mean fitness of older males' offspring (Johnson & Gemmell, 2012;Johnson et al, 2018;Preston, Saint Jalme, Hingrat, Lacroix, & Sorci, 2015;Radwan, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…But pre-copulatory and post-copulatory sexual selection can favour different traits (Evans & Garcia-Gonzalez, 2016), so it is unclear whether a female preference for older males translates into greater male reproductive success, or higher female fitness. In particular, older males might produce ejaculates that are less successful under sperm competition (McDonald, Spurgin, Fairfield, Richardson, & Pizzari, 2017), or might be less fertile thereby lowering the reproductive output of monogamous females (Carazo, Molina-Vila, & Font, 2011;Dean et al, 2010). Furthermore, the accumulation of germline mutations might reduce the mean fitness of older males' offspring (Johnson & Gemmell, 2012;Johnson et al, 2018;Preston, Saint Jalme, Hingrat, Lacroix, & Sorci, 2015;Radwan, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…We would not necessarily expect to find a difference between comparisons of precopulatory success with post‐copulatory outcome, as opposed to associating post‐copulatory outcome with precopulatory success. However, most studies in other species have found that precopulatory success is a good predictor of post‐copulatory outcome (Evans, Zane, Francescato, & Pilastro, ; Hosken, Taylor, Hoyle, Higgins, & Wedell, ; Lewis & Austad, ; Polak & Simmons, ; Sbilordo & Martin, ; McDonald, Spurgin, Fairfield, Richardson, Pizzari, ), although it matters which traits are considered (Ala‐Honkola & Manier, ). Here, however, we did not find an association between sperm length and premating success, in concordance with Droge‐Young, Manier, Lüpold, Belote, and Pitnick () and Travers et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies in other species have found that precopulatory success is a good predictor of post-copulatory outcome (Evans, Zane, Francescato, & Pilastro, 2003;Hosken, Taylor, Hoyle, Higgins, & Wedell, 2008;Lewis & Austad, 1994;Polak & Simmons, 2009;Sbilordo & Martin, 2014;McDonald, Spurgin, Fairfield, Richardson, Pizzari, 2017), although it matters which traits are considered (Ala- . Here, however, we did not find an association between sperm length and premating success, in concordance with Droge-Young, Manier, Lüpold, Belote, and Pitnick (2012) and Travers et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several of these steps are mediated by components of the male ejaculate (Box 1). Decreases in male ability to elicit favourable female post-mating responses result in reduced paternity shares for older males (McDonald et al 2017.…”
Section: Senescence Of Male Post-mating Traitsmentioning
confidence: 99%
“…It can be measured as a decline in mating activity and fertilisation success with increasing age and is often due to somatic changes, like decreased hormonal levels leading to increased dysfunction or less agile courtship resulting in lost mating opportunities. To give some brief examples, in fowl Gallus gallus, older males are less aggressive, resulting in fewer matings and reduced reproductive success as aggression is one important determinant of male mating success (McDonald et al 2017). Apart from behaviour, a reduced investment in sexual ornaments, as observed in the decreased comb size in ageing fowl (Cornwallis et al 2014) or duller foot colour in the blue-footed booby Sula nebouxii (Velando et al 2011), can result in active discrimination by females.…”
mentioning
confidence: 99%